2006
DOI: 10.1002/jcp.20833
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of pRb2/p130, VEGF, EZH2, p53, p16INK4A, p27KIP1, p21WAF1, Ki‐67 expression patterns in gastric cancer

Abstract: Although the considerable progress against gastric cancer, it remains a complex lethal disease defined by peculiar histological and molecular features. The purpose of the present study was to investigate pRb2/p130, VEGF, EZH2, p53, p16INK4A, p27KIP1, p21WAF1, Ki‐67 expressions, and analyze their possible correlations with clinicopathological factors. The expression patterns were examined by immunohistochemistry in 47 patients, 27 evaluated of intestinal‐type, and 20 of diffuse‐type, with a mean follow up of 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 41 publications
9
60
1
Order By: Relevance
“…In the present study, 64% of the cases expressed high levels of EZH 2, and this finding is in good agreement with reports by other teams [27,28]. Additionally, EZH 2 expression correlated with higher levels of p53 (46%) and Ki-67 (48%).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, 64% of the cases expressed high levels of EZH 2, and this finding is in good agreement with reports by other teams [27,28]. Additionally, EZH 2 expression correlated with higher levels of p53 (46%) and Ki-67 (48%).…”
Section: Discussionsupporting
confidence: 82%
“…The search for molecular factors highly correlated with prognosis may lead to the discovery of factors that can help to predict patient survival [1,2]. Recently, EZH 2 has been found to be involved in cell cycle regulation, and a significant association has been demonstrated between EZH 2 expression and tumor cell proliferation as well as features of aggressive tumor behavior and reduced survival [27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…3C, there were no clear increases in p53 and p21 in all the cells treated with CIP2A siRNA compared with the control cells. In addition, to corroborate the above results, we determined the phosphorylation of p53 at Ser 15 , a marker for p53 activation, using its specific antibody. The phosphorylated p53 signal at this residual was undetectable in both AGS and HCT116p53+/+ cells (data not shown), in good accordance with unchanged total p53 levels.…”
Section: Resultsmentioning
confidence: 67%
“…Some studies on the expression of molecular markers in gastric cancer revealed that p21 expression was positively correlated with the expression level of p27 [21]. It has been postulated that the growth-inhibitory activity of p27 and p21 may be modulated in advanced tumors through inactivation [22,23].…”
Section: Discussionmentioning
confidence: 99%